Magnesium dietary intake modulates blood lipid levels and atherogenesis. - Altura, B T (1990)
In this study, we have examined the effects of variation in dietary Mg on the atherogenic process. Oral supplementation of rabbits fed a high cholesterol diet (1% or 2%) with the Mg salt magnesium aspartate hydrochloride (Magnesiocard) (i) lowers the level of serum cholesterol and triglycerides in normal (25-35%) as well as atherosclerotic (20-40%) animals and (ii) attenuates the atherosclerotic process markedly. In addition, we found that dietary deficiency of Mg augments atherogenesis markedly and stimulates (or activates) macrophages of the reticuloendothelial system. Evidence is presented to indicate that the hypercholesterolemic state may cause the loss of Mg from soft tissues to the serum, thereby masking an underlying Mg deficiency.